TUTAK DAĞI (ŞEBİNKARAHİSAR) GÜNEY BATISINDAKİ PB-ZN YATAKLARI - ŞAŞMAZ, AHMET (Fırat Üniveristesi, 1993)
Doktora Tezi TUTAK DA?I (ŞEBfNKARAHİSAR-GİRESUN) GÜNEYBATISINDAKİ Pb-Zn YATAKLARI Ahmet şaşmaz Fi rai Üniversitesi Fen Bilimleri Enstitüsü Jeoloji Mühendisliği Anebilim Dalı 1993, Sayfa: 97 Tutak Dağı güneybatısındaki Pb-Zn yatakları, Doğu Karadeniz Bölgesinde, Pontidler Tektonik Birliği olarak bilinen kuşağın güneyinde ve Şebinkarahisar'ın yaklaşık 20 km. kuzeybatısında yer almaktadır. Bölgede İnler Yaylası, Mekedüzü, Dereköy ve Sübak yörelerinde izlenen cevherleşmeler d8mar tipi cevherleşmeler olup, Doğu Karadeniz metalojenik provensinin bir parçası niteliğindedir. Yörede Üst Kretase'den Pllyo-kuvaterner'e kadar değişen zaman aralıklarında oluşmuş volkanik, plutonik ve sedimanter kayaçlar bulunmaktadır. Bu birimler yaşlıdan gence doğru şöyle sıralanmaktadır; Üst Kretase yaşlı volkanitler (dasit, andezit, piroklastitler) ve karbonatlı kumtaşlan. Üst Kretase- Paleosen yaşlı graMtoyldler, Eosen volkanitleri (andezit, bazalt, trakiandezit ve tüf), Oligo- miyosen yaşlı jipsli seri (jips ve çamurtaşı) ve Pliyo-kuvaterner yaşlı volkanitler (andezit). İnceleme alanı Üst Kretase ve sonrasında yoğun bir tektonizmanın etkisi altında kalmıştır. Bölgedeki fayların doğrultuları KD-GB ve KB-GD şeklindedir. KD-GB doğrultul u feylar genellikle cevherli ve Eosen öncesi tektonik hareketler sonucu oluşmuş iken, KB-GD doğrultulu faylar ise cevhersizdir ve Eosen sonrasında meydana gelmiştir.M Yörede izlenen cevherleşmeler, inceleme alam m verevine kesen KD-GB doğrultulu, yo

Ill ABSTRACT Ph.D Thesis THE Pb-Zn ORE DEPOSITS IN THE AREA SOUTHWEST OF TUTAK MOUNTAI N (Şebinkarahisar-Giresun). Ahmet ŞAŞMAZ Fırat University Graduate School of Natural and Applied Sciences Department of Geological Engineering 1993, Page: 97 The Pb-Zn ore deposits of the area southwest of Tutak Mountain are situated in Eastern Black Sea Region, in the southern parts of the Pontids Tectonic Unit and in roughly 20 km.s northwest of Şebinkarahisar township. The ore deposits are studied in four sectors; İnler Yaylası, Mekedüzü, Dereköy and Sübak and mineralizations are vein type. The area is a part of Eastern Black Sea metellogenic province. The area is made up of volcanic, plutonic and sedimentary rocks of Upper Cretaceous to Plio-Quarternary. These lithologies are as follows; Upper Cretaceous volcanics (dacites, andesites, pi yroclastics) and carbonaceous sandstones, Upper Cretaceous-Paleogene granitoids, Eocene volcanics (andesites, basalts,trachiandesites and tuffites), Oligo- Miocene gypsifrous series (gypsium and mudstone), and Plio-Quarternary volcanics (andesite). The studied area has been subjected to Intense tectonic movements during Upper Cretaceous and later. Two main fault systems strike NE-SW and NW-SE. The NE-SW strikingIV fault zone generally mineralized and Pre- Eocene aged and the NW-SE striking ones are post Eocene aged and not mineralized. The mineralizations occur within a broad fault zone which strikes NE-SW. This 250-300 m.s wide and 1.5-2 km.s long zone is faulted intensely, mineralized and altered. The intensity of alteration changes vertical y and horizontally. In İnler Yaylası sector dominant alterations are carbonatization+ silisification and epidotization+chloritization+silisificetion and these alteration types vertically occur several times. The repetition should be as a consequence of compositional variations of volcanic rocks. The main alterations In the studied area are silisification, carbonatization, chloritization, argillization, epidotization and sericizstion. These alterations indicate a low to medium temperature formation. In northeastern end of faulted and altered zone inler Yaylası sector, from this sector towards southwest, Mekedüzü, Odalar Yaylası, Dereköy and Sübak sectors are situated. The ore minerals of the studied area are; sphalerite, galena, pyrite, chalcopyrite, fahlore group minerals, enargite, linneite, pyrrhotite, calcocite-covellite, klaprotite, tetradymite- tellurobismuthinite, Bi-fehlore groups minerals, altaite, gold, magnetite and hematite. The ore minerals of the İnler Yaylası sector show higher formations temperature textures than the minerals of other sectors. Gangue mineral are quartz, calcite, clay minerals, chlorite, hematite and baryite. The principal metallic elements of the mineralizations are Zn, Pb and Cu and in lesser amounts Cd, Ag, Sb, As and Bi.
The Pb-Zn ore deposits in the area southwest of Tutak Mountain (Şebinkarahisar-Giresun)
Keywords: Jeoloji Mühendisliği; Geological Engineering